Perubahan Penggunaan Lahan dan Kesesuaiannya Terhadap RDTR di Wilayah Peri-Urban (Studi Kasus: Kecamatan Mlati) - Eko, Trigus; Rahayu, Sri (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
TheÂ disproportionÂ ofÂ supplyÂ andÂ demandÂ ofÂ landÂ oftenÂ extendsÂ citiesÂ toÂ theirÂ peri urbanÂ areasÂ reducingÂ theirÂ agriculturalÂ areas.Â ThisÂ isÂ observableÂ inÂ Yogyakartaâ€™sÂ MlatiÂ sub districtÂ whichÂ wasÂ classifiedÂ asÂ aÂ zobidekot (aÂ regionÂ dominatedÂ byÂ agriculturalÂ areas)Â butÂ lostÂ 301, 9Â acresÂ ofÂ itsÂ agriculturalÂ areasÂ duringÂ theÂ 1996â€2010Â period.Â TheÂ studyÂ reviewsÂ bothÂ theÂ changeÂ inÂ landÂ useÂ duringÂ thatÂ period;Â and theÂ mismatchesÂ between theÂ actual developmentsÂ from theÂ DetailedÂ LandÂ UseÂ Plan.Â TheÂ studyÂ analyzesÂ aerialÂ photosÂ andÂ satelliteÂ images throughÂ overlaysÂ andÂ input-outputÂ analysis,Â togetherÂ withÂ SWOTÂ analysisÂ ofÂ theÂ landÂ useÂ implementation policies.Â ResultÂ showsÂ thatÂ 10,32%Â ofÂ Mlatiâ€™sÂ landÂ useÂ changedÂ duringÂ theÂ 1996-2010Â periodÂ resultingÂ inÂ the lossÂ ofÂ 290,67Â acresÂ ofÂ agricultureÂ areasÂ withÂ asÂ muchÂ asÂ 13,12%Â convertedÂ intoÂ housingÂ areas.Â However,Â 65,%Â ofÂ itsÂ landÂ useÂ stillÂ conformsÂ toÂ theÂ PlanningÂ Document.Â TheÂ areaÂ lacksÂ legalÂ aspectÂ inÂ itsÂ landâ€useÂ planÂ policyÂ implementationÂ sinceÂ theÂ PlanningÂ DocumentÂ hasÂ notÂ beenÂ legalized.Â InstitutionalÂ aspectÂ shows consistencyÂ andÂ availabilityÂ ofÂ adequateÂ resources,Â butÂ weakÂ implementationÂ inÂ termsÂ ofÂ controlÂ andÂ law enforcement.Â Investments,Â taxÂ policyÂ andÂ illegalÂ changes ofÂ landÂ useÂ threatening theÂ policyâ€™sÂ implementation.